Synthesis of stationary polynomial filters of non-Gaussian sygnals - Игнатов, В. А.; Лeгa Ю. Г.; Первунинский, С. М. (Proceedings of National Aviation University (archive), 1999)
Solved is the problem of non-linear filter synthesis in stationary class polynomial graded operators. Received are analytical correlations, which simplify the analysis of filter characteristics